THE IMPROVEMENT OF BEPANG CAKE PRODUCTION QUALITY BY AN INDEPENDENT INSTITUTION THAT WORKS ON THE COMMUNITY (LM3) - Grace. F. E. Suoth; Maxi Tendean (LPPM UNIMA, 2020)
The Community Service program entitled The Improvement of Bepang Cake Quality Production and Marketing is focused on 4 main activities, namely (1) counseling on institutional strengthening and group members as partners, (2) counseling on dialogue strategies to equalize perceptions, (3) training on management map preparation Bepang cake product development problems, and (4) training on the preparation of a roadmap for the management of problems developing Bepang cake products in order to improve product quality. These activities are aimed at (1) identifying and managing problems related to institutions and partner group members, (2) providing knowledge / insights about common perceptions strategies, in order to reach an agreement between institutional leaders and members regarding the management of institutional problems and members. , as well as improving the quality and marketing of Bepang cakes, (3) providing knowledge / insights to partners on how to manage group problems, in the form of problem management maps, and (4) roadmaps for implementing institutional and member strengthening programs, as well as quality improvement programs. and product marketing to provide clear directions for program implementation, carry out assistance, monitor and evaluate work processes and results. The final goal is to empower members of partner organizations / groups to resume business, improve the quality of production and marketing of Bepang cakes. Specific targets are (1) the spirit of group members' efforts to revive, (2) quality products, (3) varied flavors, (4) attractive packaging, (5) favorable prices, (6) independence and responsibility in doing business. . The method used is the lecture method, participatory method. The results are as follows: Phase I, institutional strengthening of group members (LM3) through counseling activities on management systems, training as a basis for being able to produce outputs as intellectual property rights how to seek innovations to increase the quality of Bepang cake production, including Industrial product design (draft ) so that it is feasible to sell at a higher price and how to independently break through the accessibility of marketing at the national, even global level. The second stage is evaluating the results of work in developing the processing of Cakes Bepang products that are of higher quality and accompanying the search for marketing accessibility. The 3rd stage, improving the quality of Industrial product design technology, so that it is feasible to sell at a higher price and how to independently break through better marketing accessibility at the national and global levels